An Analysis Of Metaphors Found In Aku Ini Binatang Jalang By Chairil Anwar (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This research aims to analyze the types and meanings of metaphors found in selected poems by Chairil Anwar based on Goatly’s theory of metaphor. The objectives of this study are to identify the kinds of metaphors used and to interpret their meanings in each poem. This research employed a qualitative descriptive method. The data were collected from ten selected poems, namely Aku, Sajak Putih, Diponegoro, Penghidupan, Suara Malam, Catetan Tahun 1945, Aku Berada Kembali, Cintaku Jauh di Pulau, Senja di Pelabuhan Kecil, and Derai-derai Cemara. The data were analyzed by classifying the metaphors into active metaphor, subjective metaphor, asymmetric metaphor, dead metaphor, and mimetic metaphor according to Goatly’s framework. The findings show that Chairil Anwar dominantly uses active metaphors to express strong emotions, rebellion, struggle, and existential awareness. Subjective metaphors are frequently used to convey personal feelings and psychological conditions. Asymmetric metaphors reflect power relations, conflict, and life struggles, while dead metaphors indicate expressions that have become conventional in meaning. Mimetic metaphors are used to create imaginative and dramatic imagery in the poems. The analysis reveals that metaphors play an important role in strengthening meaning, emotional intensity, and poetic expression in Chairil Anwar’s works. This study contributes to a deeper understanding of metaphor analysis in literary studies, especially in Indonesian poetry. It is expected that this research can enrich readers’ comprehension of figurative language and provide references for future researchers who are interested in metaphor studies using Goatly’s theory.
Keywords: Metaphor; Goatly’s Theory; Meaning; Poetry Analysis; Chairil Anwar